Potential of the quality of life (QoL) tool for patient profiling in paralytical strabismus (Ukrainian Journal of Ophthalmology, 2026)
Backup: To the best of our knowledge, there is no ocular motility disorder (OMD)-specific quality of life (QoL) tool, OMD-specific scale or method for patient profiling during treatment.Purpose: To develop an OMD-specific QoL assessment method in an effort to objectify treatment outcomes and to perform patient profiling during treatment.Material and Methods: We retrospectively analyzed outcomes among 240 patients (109 women and 131 men; aged 18 to 78 years; mean age, 36 ± 4.2 years) with OMD who received inpatient treatment at the Romodanov Neurosurgery Institute between 2004 and 2016. Out of these patients, 108 underwent surgeries for ruptured saccular supraclinoid internal carotid artery aneurysm, 65 underwent tumor removal (including: acoustic neurinoma, n = 23; pituitary adenoma, n = 26; and meningioma, n = 16) and 67 were treated non-surgically for craniocerebral trauma. Rehabilitative treatment was done in all patients (in operated-on patients, it was done early after surgery).Results and Discussion: We developed OMD-specific score assessment method and QoL scale involving a number of indices related to neurological symptoms, as well as to physical, psychic and social status of patients. A total OMD-specific QoL score of 0–15 is considered a poor (or low) QoL; 16–30, a moderate (or good) QoL; and 31–45, a high QoL. Not only the extent of damage to cranial nerves III, IV, and VI, but also the impact of physical handicap on the patient’s activities and on his functional abilities is assessed.Conclusion: Application of the OMD-specific QoL assessment method involving the QoL scale in clinical practice makes it possible to objectify treatment outcomes and facilitates patient profiling during treatment.
Keywords: rehabilitative treatment; ocular motility disorders; paralytical strabismus; quality of life